2015
DOI: 10.1161/hypertensionaha.115.05934
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Volume in Normotensive Formerly Preeclamptic Women Predisposes to Hypertension

Abstract: P reeclampsia is a serious hypertensive pregnancy disorder complicating 2% to 5% of all pregnancies. Preeclampsia is characterized by hypertension and proteinuria after 20 weeks of gestation. Women with a history of preeclampsia are at increased risk to develop early onset cardiovascular disease (CVD) later in life when compared with women who had an uneventful pregnancy.1 Therefore, in 2011, the American Heart Association added preeclampsia to the list of risk factors for developing CVD.2 The mechanistic expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Five studies found higher risk of antihypertensive medication use when pre‐eclampsia was recurrent compared with a single complicated pregnancy and when compared with women with uncomplicated pregnancy only . Two smaller studies looked at the proportion of recurrent pre‐eclampsia in women who were hypertensive at follow up after having had pre‐eclampsia in the index pregnancy and found conflicting results . Three studies observed women who went on to have subsequent pregnancies after pre‐eclampsia, in the first two articles a nonsignificant association was mentioned in the text .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies found higher risk of antihypertensive medication use when pre‐eclampsia was recurrent compared with a single complicated pregnancy and when compared with women with uncomplicated pregnancy only . Two smaller studies looked at the proportion of recurrent pre‐eclampsia in women who were hypertensive at follow up after having had pre‐eclampsia in the index pregnancy and found conflicting results . Three studies observed women who went on to have subsequent pregnancies after pre‐eclampsia, in the first two articles a nonsignificant association was mentioned in the text .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies within this review discussed timing as a factor in determining cardiovascular risk, morbidity and mortality. When looking at cardiovascular risk markers, studies found significant correlation after many years of follow up, even though these markers may not be apparent soon after pregnancy . A few studies analysed time between pre‐eclampsia and CVD in their set‐up, reporting a significantly shorter time to cardiovascular events in the recurrent group with a significantly accelerated disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma volume showed a strong positive correlation with body weight, lean body mass, and body surface area, but no correlations with plasma osmolality, blood pressure (systolic and diastolic blood pressure), or reproductive hormones (estradiol or progesterone). Though plasma volume measures often focus on changes during pregnancy, recent studies have shown that prepregnant plasma volume could be an important factor in predicting risk of recurrent preeclampsia, recurrent pregnancy loss, and risk of preterm delivery (Donckers et al, 2012; Scholten et al, 2011; Aardenburg et al, 2003, 2006; Donckers et al, 2012; Scholten et al, 2011, 2015; Spaanderman et al, 2001; Stekkinger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of estrogen and progesterone, as well as changes in the renin‐angiotensin‐aldosterone system (RAAS), play a role in the increase in plasma volume across gestation. Compared with normal plasma volume, women with low plasma volume are at an increased risk of gestational hypertension, recurrent preeclampsia, recurrent pregnancy loss, and preterm delivery (Aardenburg, Spaanderman, Eijndhoven, Leeuw, & Peeters, 2006; Aardenburg et al, 2003; Donckers et al, 2012; Scholten et al, 2011, 2015; Spaanderman et al, 2001; Stekkinger, Scholten, Heidema, & Spaanderman, 2015). While plasma volume expansion in pregnancy has long been established, our knowledge of plasma volume across the menstrual cycle is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, there have been additional studies of plasma volume, but not many. Adverse pregnancy outcomes, including hypertensive disorders of pregnancy, have been linked to reduced plasma volume expansion during pregnancy [4][5][6][7]. Plasma volume in the third trimester [8][9][10] and total plasma volume expansion [10][11][12][13] are both positively associated with birthweight.…”
Section: Introductionmentioning
confidence: 99%